An evaluation of efficacy of the auto-dissemination technique as a tool for Aedes aegypti control in Madeira, Portugal - Gonçalo Seixas; Richard E. L. Paul; Bianca Pires; Gonçalo Alves; Ana de Jesus; Ana-Clara Silva; Gregor J. Devine; Carla A. Sousa (Parasites & Vectors, 2019)
Abstract Background The frequency and intensity of arboviral epidemics is steadily increasing and posing an intractable public health burden. Current vector control methods are proving ineffectual and despite progress in the development of high technology approaches, there is an urgent need for the development of tools for immediate implementation. Several studies suggest that the auto-dissemination of pyriproxyfen (PPF) is a promising new approach to larviciding although there is little detail on the conditions under which it is optimally effective. Here, we evaluate the efficacy of the approach in urban and rural sites in Madeira, Portugal. Results Auto-dissemination of PPF through adapted Biogents Sentinel traps (BGSTs) resulted in a modest but consistent impact on both juvenile and adult mosquito populations, but with considerable spatial heterogeneity. This heterogeneity was related to the distance from the BGST dissemination station as well as the local density of adult mosquitoes. There was evidence that the impact of PPF was cumulative over time both locally and with gradual spatial expansion. Conclusions The density of adult mosquitoes and the spatial distribution of dissemination devices are key factors in mediating efficacy. In addition, urban topography may affect the efficiency of auto-dissemination by impeding adult mosquito dispersal. Further studies in a range of urban landscapes are necessary to guide optimal strategies for the implementation of this potentially efficacious and cost-effective approach to larviciding.